High Prevalence of Chronic Pain With Neuropathic Characteristics After Open Reduction and Internal Fixation of Ankle Fractures. (September 2017) - Rbia, Nadia; van der Vlies, Cornelis H.; Cleffken, Berry I.; Selles, Ruud W.; Hovius, Steven E. R.; Nijhuis, Tim H. J.
Background: Unstable ankle fractures require treatment with open reduction and internal fixation (ORIF). Long-term functional outcome is satisfying in most patients; however, a number of patients have persistent complaints. Superficial nerve complications following ankle surgery may be the cause of chronic pain and disability. Methods: In this observational retrospective survey, a cohort of 527 women and men, who underwent ORIF in the period from January 2007 to January 2014, were invited to an online questionnaire. Pain symptoms were assessed using the McGill Pain Questionnaire (MPQ) and the Douleur Neuropathic en 4 Questions (DN4) Questionnaire. Descriptive statistics were used to present patient characteristics; a logistic regression model was used to analyze prognostic factors of neuropathic pain. A total of 271 patients completed the questionnaire. Mean follow-up period was 5.8 years (±1.9). Results: Persistent neuropathic pain symptoms were present in 61 of all patients, and 51 of these patients reported an impaired quality of life caused by their symptoms. In univariate analysis, the following parameters were associated with neuropathic pain: age, hypertension, a thyroid disorder, lower back pain, fracture dislocations, and late complications such as nonunion, posttraumatic arthritis, or osteochondral injury. In multivariate analysis, an age between 40 and 60 years was found to be a significant predictor of neuropathic pain. Hypertension, dislocation, and late complications were significant predictors of persistent pain without neuropathic characteristics. Conclusion: The present study demonstrated a prevalence of persistent neuropathic pain symptoms after ORIF for ankle fractures in 23% of the respondents, which caused an impaired health-related quality of life. We identified 4 significant predictors of chronic and neuropathic pain after ORIF. This knowledge may aid the treating surgeon to identify patients who are at increased risk of persistent postoperative neuropathic pain and may affect the treatment of pain in these patients. Level of Evidence: Level IV, retrospective case series.